1975
DOI: 10.1111/j.1545-5300.1975.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Personal Network in Clinical Practice

Abstract: The practice of clinicians in all the helping professions has undergone wide‐ranging change in the past two decades. This change has been uneven and halting, but an essential aspect has been a movement toward a wider arena of practice, including a variety of social network practices. The concept of personal network holds high promise for becoming a major unifying framework in clinical practice: as an analytic viewpoint, as a schema for problem location, and as an arena of practice and research. This paper will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

1979
1979
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 19 publications
0
16
0
3
Order By: Relevance
“…That is, it is likely that social networks operate most effectively when an optimal balance is struck between an internal support orientation and an external information-seeking or bridging orientation, while an exclusive strategy of maximizing one or the other is maladaptive. Erickson (1975) has hypothesized that elaborate service networks for client support are preceded by severely truncated kinship and friendship networks. This may suggest that human service providers enter the social vacuum surrounding some of their clients in a way which severely and permanently shifts a network away from this optimal balance.…”
Section: Discussionmentioning
confidence: 99%
“…That is, it is likely that social networks operate most effectively when an optimal balance is struck between an internal support orientation and an external information-seeking or bridging orientation, while an exclusive strategy of maximizing one or the other is maladaptive. Erickson (1975) has hypothesized that elaborate service networks for client support are preceded by severely truncated kinship and friendship networks. This may suggest that human service providers enter the social vacuum surrounding some of their clients in a way which severely and permanently shifts a network away from this optimal balance.…”
Section: Discussionmentioning
confidence: 99%
“…One large survey study reported a significant relationship between SN density and the reported availability of everyday and crisis support (Wellman et al, 1973). Increasing SN density appears to have been a goal of those who have made crisis interventions into SNs (Erickson, 1975). Tolsdorf (1976) did not find any significant difference in the density of the SNs of hospitalized schizophrenics as compared to nonpsychiatric hospital patients.…”
Section: Study #2: the Social Network As A Natural Support Systemmentioning
confidence: 99%
“…Social networks, for example, were seen as accounting for much spontaneous remission of psychological symptoms (Bergin, 1971), as well as making an important contribution to t h e rehabilitation of exhospital patients (Fairweather, Sanders, Cressler, & Maynard, 1969). Interventions directly into the assembled SNs of psychiatric patieflts have been reported by a number of crisis-oriented family therapists (e.g., Erickson, 1975;Speck & Attneave, 1973),…”
mentioning
confidence: 99%
“…Social networks have been regarded as a promising concept for becoming a unifying framework in clinical practice since 1970s [30]. To date, social network concepts and techniques have been applied in clinical and hospital settings [3], for doctors and nurses to deliver better quality care [19,65] and physician utilisation of medical information systems [4].…”
Section: Social Network and Process Of Carementioning
confidence: 99%